From a Real Place and Real People: Interview with Mississippi Damned Writer/Director Tina Mabry - Moore, Marlon Rachquel (Black Camera, 2011)
Marlon Rachquel Moore interviews emerging independent filmmaker Tina Mabry about her southern upbringing, racial and sexual consciousness, and the joys and turbulence of bringing her first feature-length film, Mississippi Damned, to the silver screen. Mississippi Damned is based on Mabry's family and set in her hometown of Tupelo, Mississippi.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Num Pages: 65-77 Place: Austin, United States
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Uplift Cinema: The Emergence of African American Film and the Possibility of Black Modernity - Field, Allyson Nadia (Duke University Press, 2015)
Allyson Nadia Field recovers the forgotten body of African American filmmaking from the 1910s which she calls uplift cinema. These films were part of the racial uplift project, which emphasized education, respectability, and self-sufficiency, and weren't only responses to racist representations of African Americans in other films.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

"Rock-a-Bye, Baby!": Black Women Disrupting Gangs and Constructing Hip-Hop Gangsta Films - Smith-Shomade, Beretta E. (Cinema Journal, 2003)
This essay examines the cultural specificity of the gangster genre. In hip-hop gangsta films, the inclusion of black women as central to the gangster business not only transforms the gangster genre but, more important, adheres to black cultural norms. The films New Jack City, Sugar Hill, and Set It Off serve as case studies.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

We are here but are we Queer?: Lesbian Filmmaking versus Queer Cinema Conference, London, 12 March 1994 - Florence, Penny (Screen, 1994)
Num Pages: 297-300
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Straight Skin, Gay Masks and Pretending to Be Gay on Screen - Padva, Gilad (Routledge, 2020)
Straight Skin, Gay Masks and Pretending to Be Gay on Screen examines cinematic depictions of pretending-to-be-gay, assessing performances that not only reflect heteronormative and explicitly homophobic attitudes, but also offer depictions of gay selfhood with more nuanced multidirectional identifications. The case of straight protagonists pretending to be gay on screen is the ideal context in which to study unanticipated progressivity and dissidence in regard to cultural construction of human sexualities in the face of theatricalized epistemological collapse. Teasing apart the dynamics of depictions of both sexual stability and fluidity in cinematic images of men pretending to be gay offers new insights into such salient issues as sexual vulnerability and dynamics and long-term queer visibility in a politically complicated mass culture which is mostly produced in a heteronormative and even hostile cultural environment. Additionally, this book initially examines queer uses of sexuality masquerade in Alternate Gay World Cinema that allegorically features a world pretending to be gay, in which straights are harassed and persecuted, in order to expose the tragic consequences of sexual intolerance. Films and TV series examined as part of the analysis include The Gay Deceivers, Victor/Victoria, Happy Texas, William Friedkin’s Cruising and many other straight and gay screens. This is a fascinating and important study relevant to students and researchers in Film Studies, Media Studies, Gender Studies, Queer Studies, Sexuality Studies, Communication Studies and Cultural Studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Narrating Our History: An Introduction - Harris, Thomas Allen (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Around 1994 or 1995 I came across a call for articles for an anthology to be published by the XII Black International Cinema , documenting ten years of the festival and associated activities, 1986– 95. The request asked for articles and film lists from an international and intercultural group of scholars and filmmakers, and I thought this was an opportunity to document the exciting and pioneering work that was being done by a community of emerging Black lesbian and gay film-and video makers at the time.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Identity and Performance in Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography - Heitner, Devorah (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In novel ways, and from a surprising location, Yvonne Welbon’s Remembering Wei-Yi Fang, Remembering Myself: An Autobiography (1995) explores some of the same dilemmas that earlier African American expatriate artists promulgated, using their time abroad as a win dow onto America, while relishing the nurturing possibilities of partial escape from American racism. Some of the most complex and insightful observations about America and American racism have been crafted by African American expatriate artists such as James Baldwin and Josephine Baker. These artists’ depictions of their encounters abroad complicate our understandings of American identity and American racism.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Few of My Favourite Things: The Feiticeiro/a as Foundation for ‘Pervert’ Characterisation - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A non-foundationalist construct for the Feiticeiro/a character that assumes neither an essentialist nature nor a determinist set of activities is possible. This does not prescribe a ‘type’ of ‘pervert’ character, but instead delineates an epistemic framing for a Feiticeiro/a character. This chapter explores an etymologically based semiotic approach to character construction that accounts for a Derridean view that language is constituted by binary reciprocal delimitations and for a view of sex as a dereified expression of materialised instances of engagement by sexual subjects, in terms of which sexuality is rendered as an opened-outward and connected function. The chapter further deals with an approach based in an empathic engagement between audiences and Feiticeiro/a characters, which is apposite for audiences identifying with but not necessarily liking characters. The chapter closes the volume’s argument around how transgressive, sexually focused Feiticeiro/a characters might productively be constructed in terms other than of essences and determinist actions, but in terms of ‘meaning’ found in the points of connection between heterogeneous bodily surfaces.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Anthropologically Present ‘Perverts’: Re-instating the Feitiço as the Feiticeiro/a - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A post-humanist lens is useful as a starting-point to remedy the absenting and invisibilising effects of sexological epistemologies for the purposes of conceiving a constitution of ‘pervert’ filmic characters, since certain strains of existential thinking have a meta-theoretical pliancy that is useful for reflecting the non-binary character of complex people beyond simple identity categories, across a range of types and styles of filmic products. If matched with a semiological approach such as that espoused by Barthes, it thereby becomes possible to manipulate signs in the form of character constructions to represent people as more than the sum of their parts and to contain deeper significations that are built into the fabric of their construction. This requires a deeper understanding of the semiotic notion of ‘semes’ as the foundation for character construction. To this end, this chapter explores how sexual ‘perversion’ as reflected in notion of the ‘feitiço’ might serve as a foundation for a new episteme for ‘perverse’ characters, as the Feiticeiro/a as ‘sorcerer/sorceress’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Psychoanalytic Absence: Freudian Object-Focus and the Resultant ‘Pervert Sans-Corpus’ - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The notion of ‘perversity’ suggests inherent transgressiveness. However, a focus on practices does not help identify who filmic characters are in ways that might inform a paradigm for character identity suitable for translation into a visual medium. Failing to achieve this clarity, ‘perverts’ often end up as ‘ambulatory objects’ at once imagined and defined by what is not present. This chapter engages how this manifests in the nineteenth-century sexological discourses that reflected perverse prurience in terms of assumptions that all entities might be empirically identifiable in the same way that material phenomena can be perceived by means of the senses, which is especially visible in the various incarnations of Freudian constructs of ‘fetishism’ that refuse personal agency through reliance on a range of psychodynamic constructs.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The Internally Coherent Feiticeiro/a: A Structure not a Substance - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
The categories for ‘perversion’ in the World Health Organization’s ICD fail to describe people and their practices, thereby obscuring the remarkable singularity of individuals and diversity of groups. Instead, they prescribe heteronormative sexual behaviour, which is unhelpful as a foundation for the Feiticeiro/a character. This chapter explores an alternative epistemic construct, as becomes available in the notion of a focalising character, which reflects a ‘semic’ construct that negates the notion of a ‘pervert’ character as a substance, but instead embraces the notion of a Feiticeiro/a character as a structure. The chapter further explores the philosophical nature of this structure as it relates to the thematic elements of a narrative whilst engaging in believable activities in a material world. The chapter then suggests an approach to structure based in a phenomenological notion of the replacement of ‘substance’ with ‘form’/‘structure’ as the foundation of meaning.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Towards an Episteme for the Feiticeiro/a: Realism in Character Construction - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
An episteme for the Feiticeiro/a as a filmic character who is ‘perverse’ needs a form if it is to be useful to writers wanting to construct complex transgressive sexual characters. The beginnings of this framing are productively associated with the semiotic notion of ‘connotation’. This chapter explores what is meant by complexity in character construction and suggests a framing focused on character as an embodied being as a helpful starting-point for an episteme for characterological ‘perversion’. The chapter explores this as a non-foundationalist framing that transcends problematic Cartesian distinctions, concrete object materiality and woolly broad-stroke statements of a disembodied discursive constitution of social and personal experience.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Writing ‘Perverse’ Behaviour for the Feiticeiro/a: Revisioning the ICD Diagnostic Criteria - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
If the Feiticeiro/a as a psychologically defined and complex character is to be seen as an embodied form/structure (not substance) that exists in dialectical relationships between self, other and discursive constructions of society, a clearer indication should be made about what kinds of behaviours or actions he/she should engage in. This chapter explores how psychiatric diagnostic criteria fail to provide assistance, despite professing to authoritatively mark stable, reliable and accurate epistemic boundaries to sexual activity. The chapter thereby addresses questions of the description of actions versus the demarcation of thoughts, objects, feelings and time as invisible and abstracted notions that are virtually the opposite of what is useful for an episteme for the Feiticeiro/a. It also approaches how the diagnostic criteria codify ‘perverse’ activity in determinist terms, thereby insidiously refusing an epistemic construct of action into which is built an acknowledgement of the behaviours of the Feiticeiro/a as a complex subjectivity.
Keywords: 1-Cinéma; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

African American Cinema Through Black Lives Consciousness - Reid, Mark A. (Wayne State University Press, 2019)
"African American Cinema through Black Lives Consciousness uses critical race theory to discuss American films that embrace contemporary issues of race, sexuality, class, and gender. Its linear history chronicles black-oriented narrative film from post-World War II through the presidential administration of Barack Obama. Editor Mark A. Reid has assembled a stellar list of contributors who approach their film analyses as an intersectional practice that combines queer theory, feminism/womanism, and class analytical strategies alongside conventional film history and theory. Taken together, the essays invigorate a "Black Lives Consciousness," which speaks to the value of black bodies that might be traumatized and those bodies that are coming into being-ness through intersectional theoretical analysis and everyday activism. The volume includes essays such as Gerald R. Butters's, "Blaxploitation Film," which charts the genre and its uses of violence, sex, and misogyny to provoke a realization of other philosophical and sociopolitical themes that concern intersectional praxis. Dan Flory's "African-American Film Noir" explains the intertextual-fictional and socio-ecological-dynamics of black action films. Melba J. Boyd's essay, "'Who's that Nigga on that Nag?': Django Unchained and the Return of the Blaxploitation Hero," argues that the film provides cultural and historical insight, "signifies" on blackface stereotypes, and chastises Hollywood cinema's misrepresentation of slavery. African American Cinema through Black Lives Consciousness embraces varied social experiences within a cinematic Black Lives Consciousness intersectionality. The interdisciplinary quality of the anthology makes it approachable to students and scholars of fields ranging from film to culture to African American studies alike."
Pages: x, 310 pages :
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé